Influenza season - is there anything to worry about? - Dubaj, Maciej; Słomczyńska, Katarzyna; Karczmarczyk, Marta (Journal of Education, Health and Sport, 2021)
Influenza (the flu) is an acute infectious disease caused by viruses of the Orthomyxoviridae family, causing a wide variety of symptoms in humans, ranging from mildly disturbing daily activities to life-threatening pneumonia, depending on the state of their immune system. The annual increase in the incidence of this disease is called "the flu season", which is a periodic epidemic that affects people all around the world. Despite the individual, economic and epidemiological risks associated with infection with the influenza virus, the disease is often underestimated by people. The aim of this study was to present influenza as a threat to the health of individuals and society by describing the pathomechanisms of its formation and spread, available diagnostic and therapeutic options, as well as annual vaccinations as the most effective method of disease prevention. The current publications available in online scientific databases from many countries around the world were reviewed. Despite the large number of widely available research results on influenza, it is necessary to update them every year, as well as vaccines against this disease, to popularize knowledge about it, which will enable more effective epidemiological control of influenza.